Pengaruh Media E Flashcard dalam Memahami Materi Pembelajaran IPS Siswa Kelas III UPT SPF SD Inpres Bontomanai - Winni An Nisa; Hidayah Quraisy; Fitri Yanty Muchtar (Jurnal Pustaka Cendekia Pendidikan, 2024)
This research aims to determine the influence of E Flashcard media in social studies learning for class III students. This research is quantitative research using pre-experimental design with a one group pretest-posttest design. The data in this research were analyzed using descriptive statistical analysis techniques and inferential statistics. The results show that there is an influence of E Flashcard media in understanding social studies learning for class III UPT SPF SD Inpres Bontomanai students. This is shown by the average pretest score of 62 and posttest 80. Based on the results of the independent sample t-test hypothesis test, the sig. (2-tailed) equal variance assumed obtained 0.000 which shows that 0.000 < 0.05 or in other words (H0) is rejected and (H1) is accepted, which means that there is an influence of E Flashcard media in understanding social studies learning material for class III students.